Data for "Springtime stratospheric volcanic aerosol impact on midlatitude cirrus clouds" - Sporre, Moa; Friberg, Johan (Lund University, 2021)
Here we present the datasets used in the study "Springtime stratospheric volcanic aerosol impact on midlatitude cirrus clouds" where we investigate how cirrus clouds are impacted by downwelling volcanic sulfate aerosol from the stratosphere. In one of the datasets here the cirrus microphysical properties at different temperatures are included. This dataset span the years 2008 to 2016. In the other dataset there is data about light backscattering that can be used to estimate the aerosol load in the lowermost stratosphere. This dataset span the years 2008 to 2019.

This data includes two datasets. One of them contains information about cirrus cloud microphysical properties at different temperatures. This dataset is based on products from the DARDAR (raDAR/liDAR) datasets DARDAR-CLOUD och DARDAR-NICE. The other datasets contain data of molecular and total backscattering from chosen height intervals in the lowermost stratosphere. This dataset is based on measurements from the satellite instrument CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization).

Data files are provided in NetCDF format (https://www.unidata.ucar.edu/software/netcdf/)

Dessa dataset ligger till grund för studien "Springtime stratospheric volcanic aerosol impact on midlatitude cirrus clouds" där vi undersökt hur cirrusmoln påverkas av vulkanisk sulfat aerosol som väller ner från stratosfären. I det ena datasetet finns mikrofysikaliska egenskaper för cirrusmoln på olika temperaturer mellan 2008 och 2016. I det andra datasetet finns data över ljusspridning i den lägre stratosfären. Datat över ljusspridning sträcker sig över 2008 till 2019.

Datat inkluderar två satellitdataset. Det ena har information om cirrusmolns mikrofysikaliska egenskaper vid olika temperaturer. Detta baseras på produkter från DARDAR (raDAR/liDAR) dataseten DARDAR-CLOUD och DARDAR-NICE. Det andra satellitdatasetet innehåller data över molekylär backscattering och total backscattering från ett utvalt höjdintervall i den lägre delen av stratosfären. Detta dataset baseras på mätningar från satellitinstrumentet CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization)

Datafiler finns i NetCDF-format (https://www.unidata.ucar.edu/software/netcdf/).
Data till "Springtime stratospheric volcanic aerosol impact on midlatitude cirrus clouds"
Keywords: Atmospheric conditions; Atmosfäriska förhållanden; stratospheric aerosol; stratosfärsaerosol; cirrus clouds; cirrusmoln; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi